The In Situ Hybridization Expression of Fas and Fas Ligand (FasL) in Trophoblastic tissue of Aborted Women Compared with Normal Pregnancy. - Salman, Amal H.; Hana, Dalya B.; Ahmad, Dhamraa W. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Estimation of the in situ expression of Fas and Fas ligand (FasL) in aborted women compared with normal human pregnancy . Patients and Methods: A technique utilizing in situ hybridization(ISH) was performed to detect and determine the in situ expression of Fas and Fas ligand (FasL) mRNA using paraffin embedded sections of curettage samples obtained from 42 women, who were divided into two groups: 30 women with first trimester abortion and 12 women with induced abortion as control. Results: The levels of the in situ expression of both Fas and Fas ligand (FasL) mRNA were found to be highly significant increased in group 1 as compared with group 2 (p<0.01), with a significant positive correlation between Fas; and abortion in group I , FasL & abortion in group I , and between these two parameters(Fas & FasL) (p<0.01) in group1 . Conclusions: The increasing expression of Fas and FasL trophoblasts might influence pathogenesis of first trimester abortion.